Role of waqf in education : a case study at Angsana College / Fauzul Hakim Saluddin - Saluddin, Fauzul Hakim (Academy of Contemporary Islamic Studies (ACIS), 2016)
Endowments are a very precious practice is encouraged by Islam. As one of the mechanisms of virtue, endowments quite unique compared to charity, gifts and donations for the donated property will be on 'hold' it was not spent but any benefits or returns from the use of property ownership could spent. However, there is still a lack of understanding of the concept of religious endowment, especially involving university students because they are not exposed to religious endowment. This study was conducted to identify the extent of students' understanding of the concept of UiTM Puncak Alam religious endowment, charitable institutions and the role of religious endowment effect on education. A total of 25 students from UiTM Puncak Alam campus has been selected randomly to participate in this study. This study is an attempt to determine the extent of the students' understanding of the concept of UiTM Puncak Alam religious endowment in addition to explain it. This research approach oriented target group. The first chapter describes the endowment. In addition, the statement also had religious endowment loaded in this first chapter. Not forgetting the objective, scope, objectives and importance of the study is also infused in the first chapter. The second chapter focuses on the concepts and facts related endowment itself. In the second chapter, this is the concept of waqf described in more vivid and clear. The third chapter is about the background to the institution of waqf. This means that the history of institutional development contained in this chapter. The fourth chapter analyzes related findings. It also involves the target group with the respondent, then were taken and compared according to certain standards. Finally, this chapter was closed with the conclusion of the survey and identification of the respondents' level of understanding related endowment.